The Pandemic Experience in Southeast Asia: Interface Between SARS-CoV-2, Malaria, and Dengue - Yek, Christina; Nam, Vu Sinh; Leang, Rithea; Parker, Daniel M.; Heng, Seng; Souv, Kimsan; Sovannaroth, Siv; Mayxay, Mayfong; AbuBakar, Sazaly; Sasmono, R. Tedjo; Tran, Nhu Duong; Nguyen, Hang Khanh Le; et al. (Frontiers in Tropical Diseases, 2021)
Southeast Asia (SEA) emerged relatively unscathed from the first year of the global SARS-CoV-2 pandemic, but as of July 2021 the region is experiencing a surge in case numbers primarily driven by Alpha (B.1.1.7) and subsequently the more transmissible Delta (B.1.617.2) variants. While initial disease burden was mitigated by swift government responses, favorable cultural and societal factors, the more recent rise in cases suggests an under-appreciation of prior prevalence and over-appreciation of possible cross-protective immunity from exposure to endemic viruses, and highlights the effects of vaccine rollout at varying tempos and of variable efficacy. This burgeoning crisis is further complicated by co-existence of malaria and dengue in the region, with implications of serological cross-reactivity on interpretation of SARS-CoV-2 assays and competing resource demands impacting efforts to contain both endemic and pandemic disease.